Group Elevator Control Optimization using Artificial Atom Algorithm - Erdogan Yildirim, Ayse; Karci, Ali (Ieee, 2017)
With the applications of artificial intelligence, it is possible to produce accurate and effective solutions for many problems encountered in daily life. In this study, Artificial Atom Algorithm, which is a topical algorithm, is used for optimum routing in group elevator control. The Artificial Atom Algorithm is a meta-heuristic algorithm that was improved by inspired the compounding process of atoms. With the application, it is aimed that is responded to hall calls in the most effective way by working 7 elevators in 16-storey building. The system which is designed for this purpose, offers optimum control for elevators. The total elapsed time to answer the hall calls has been minimized with the study.
2017 International Artificial Intelligence and Data Processing Symposium (IDAP) -- SEP 16-17, 2017 -- Malatya, TURKEY
Keywords: Elevator control optimization; Artificial atom algorithm; Meta-heuristic algorithm; Artificial intelligence applications